Analisis Perbandingan Persepsi Masyarakat Kota Bogor Pada Kinerja Perbankan Syariah Dan Perbankan Konvensional - Hidayat, Lukman; Marlina, Tri; ., Morita (Jurnal Ilmiah Manajemen Kesatuan, 2016)
The objective of this study is to identify the perception of atributive performance of syaria and conventional banking products considered by consumers prior tobecome costumers. Moreover, it is also aimed to analyze the comparison between the perception of attributive performance of Syaria and conventional banking products.The population are Bogor residents who have done financial transactions with both Syaria and conventional banks. The size of the sample is 100 respondents using Convenience Sampling technique. The data collection technique uses questionnaire which combines closed questions and open questions. Data are analyzed by non parametric comparison analysis. Based on data analysis, it shows that the perception of the community towards the attributive performance of Syaria banking products is in good category. However, there is no significant difference on the perception of the community towards the attributive performance of Syaria and conventional banking products.